2006
DOI: 10.1007/s10488-006-0045-3
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia, Co-occurring Substance use Disorders and Quality of Care: The Differential Effect of a Managed Behavioral Health Care Carve-out

Abstract: This study explores the differential effect of a managed behavioral health Carve-Out (CO) on outpatient treatment quality for persons with schizophrenia (SCHZ) alone and co-occurring substance use disorders (SUD) (SCHZ+SUD). We used claims data from a state Medicaid program and employed a retrospective, quasi-experimental design with logit and difference in difference formula regression models. The results show the CO was associated with greater changes in treatment quality for the SCHZ population, compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Several evaluations (Busch, Frank, Lehman, & Greenfield, 2006;Busch, 2002;Manning et al, 1999;Ray, Daugherty, & Meador, 2003) examined the impacts of carve-outs on special populations and reported mixed outcomes. Some of these found that carve-out programs had negative effects on special populations, including higher rates of discontinuity of antipsychotic medication among patients with severe mental illness in Tennessee; poorer outcomes for Medicaid recipients with schizophrenia in Utah; and decreases in psychosocial treatments for patients with schizophrenia alone and schizophrenia with co-occurring substance abuse (Ray et al, 2003).…”
Section: Comparisons Of Ffs and Managed Care Plansmentioning
confidence: 99%
“…Several evaluations (Busch, Frank, Lehman, & Greenfield, 2006;Busch, 2002;Manning et al, 1999;Ray, Daugherty, & Meador, 2003) examined the impacts of carve-outs on special populations and reported mixed outcomes. Some of these found that carve-out programs had negative effects on special populations, including higher rates of discontinuity of antipsychotic medication among patients with severe mental illness in Tennessee; poorer outcomes for Medicaid recipients with schizophrenia in Utah; and decreases in psychosocial treatments for patients with schizophrenia alone and schizophrenia with co-occurring substance abuse (Ray et al, 2003).…”
Section: Comparisons Of Ffs and Managed Care Plansmentioning
confidence: 99%
“…Others express concern about the differential impact of carve-outs on children or low-income families (38); findings of higher readmission rates for children than for other Medicaid popualtions in Callahan et al (13) and greater declines in utilization for Aid to Families with Dependent Childrenrelated groups than for other beneficiaries in Christianson et al (14) indicate that experiences in Medicaid carve-outs for children and families may differ from those of disabled adult beneficiaries. Performance may also Frank · Garfield differ for individuals who experience substance abuse problems and mental health care problems (11,56), although few studies allow for comparisons of these two types of services within the same evaluation. 8 Finally, the variation in findings may be due to ownership of carve-outs, as evidenced by Colorado's experience where larger impacts were observed under the for-profit relative to communitybased Medicaid carve-outs.…”
Section: Wwwannualreviewsorg • Behavioral Health Care Carve-outsmentioning
confidence: 99%
“…We included adults aged 18–64 years who were not dually enrolled in Medicare or a managed care plan during the 180 days before their first SGA fill. Enrollees were classified as having schizophrenia if they had at least two claims (inpatient or outpatient, on separate service dates) for schizophrenia (ICD‐9‐CM 295.x) from July 2000 to December 2006 . Enrollees were classified as having bipolar disorder if they did not have schizophrenia and had at least two claims for a bipolar spectrum disorder (ICD‐9‐CM 296.0, 296.1, 296.4–296.8) …”
Section: Methodsmentioning
confidence: 99%